Intravenous alfacalcidol improves insulin resistance in hemodialysis patients - Gunal, AI; Celiker, H; Celebi, H; Ustundag, B; Gunal, SY (Dustri-Verlag Dr Karl Feistle, 1997)
We have examined the effect of a four-week intravenous treatment with 1 alpha-hydroxyvitamin D-3 on insulin sensitivity in 14 patients on chronic hemodialysis compared with 10 healthy control subjects by the insulin tolerance test. Compared to controls, the uremic patients have featured increased levels of parathyroid hormone (1085.0 +/- 822.1 vs 74.2 +/- 8.7 pg/ml, p <0.001), insulin resistance (the rate constant for plasma glucose disappearance, K-itt: 3.1 +/- 0.5 vs 4.5 +/- 0.4%/dk, p <0.002), increased levels of insulin (30.5 +/- 7.3 vs 20.4 +/- 2.8 mu IU/ml, p <0.04) and increased levels of C-peptide (6.0 +/- 2.1 vs 3.9 +/- 12. ng/ml, p <0.001). Following treatment with 1 alpha-hydroxyvitamin D-3, levels of parathyroid hormone decreased from 1085.0 +/- 822.1 to 772.1 +/- 620.1 pg/ml (p <0.004), the K-itt values increased significantly (from 3.1 +/- 0.5 to 4.1 +/- 0.4%/dk, p <0.004) and reached the level near to that of controls, the insulin concentrations decreased from 30.5 +/- 7.3 to 28.7 +/- 9.2 mu IU/ml (p >0.05) and C-peptide concentrations increased from 6.0 +/- 2.1 to 7.5 +/- 2.5 ng/ml (p <0.02). In summary, uremic patients with secondary hyperparathyroidism developed insulin resistance and hyperinsulinemia. Intravenous 1 alpha-hydroxyvitamin D-3 treatment has improved insulin sensitivity directly or by reducing secondary hyperparathyroidism in uremic patients on chronic hemodialysis.
Keywords: chronic renal failure; insulin resistance; alfacalcidol; insulin tolerance test